An Italian Guidance Model for the Management of Suspected or Confirmed COVID-19 Patients in the Primary Care Setting - Lopes, Noemi; Vernuccio, Federica; Costantino, Claudio; Imburgia, Claudia; Gregoretti, Cesare; Salomone, Salvatore; Drago, Filippo; Lo Bianco, Giuliano (Frontiers in Public Health, 2020)
An outbreak of Severe Acute Respiratory Syndrome Coronavirus 2 started in China’s Hubei province at the end of 2019 has rapidly become a pandemic. In Italy, a great number of patients was managed in primary care setting and the role of general practitioners and physicians working in the first-aid emergency medical service has become of utmost importance to coordinate the network between the territory and hospitals during the pandemic. Aim of this manuscript is to provide a guidance model for the management of suspected, probable, or confirmed cases of SARS-CoV-2 infection in the primary care setting, from diagnosis to treatment, applying also the recommendations of the Italian Society of General Medicine. Moreover, this multidisciplinary contribution would analyze and synthetize the preventive measures to limit the spread of SARS-CoV-2 infection in the general population as well as the perspective for vaccines.